Meta-Analisis Faktor Pendorong Aktivitas Antropogenik Terhadap Karakteristik Kebakaran Hutan dan Lahan Gambut di Indonesia - Eka Wulandari; Ersa Tri Fitriasari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is the use of land in managing the land and doing environmentally friendly treatment in clearing the land. The method that was carried out by meta-analysis with 175 journal articles related to forest and land fires in Indonesia was then identified to produce an inventory of data for meta-analysis. The results of the research through an independence test between the factors driving fires from anthropogenic activities and the characteristics of fires indicate that the factor of weak law enforcement and protection in land tenure is significantly related to the characteristics of fires. The conclusions from this research are that land use rights must be clear and fair, concession holders have managed their land well and provide sanctions for those who violate the applicable regulations and the importance of developing innovations in clearing and managing peatlands without burning according to needs and providing benefits. economy, especially for small farmers, thereby reducing vertical and horizontal conflicts. Keywords: Land, Fire, Forest.